The geographical factors in function of viniculture and wine tourism development in the Tikvesh Basin - Kole Pavlov; Ace Milenkovski; Gjorgi Pavlovski (UTMS Journal of Economics, 2014)
In this effort an attempt was made to analyse the geographical factors i.e. their objective impact on viniculture and wine tourism in the renowned Tikvesh Basin, which represents a symbol of this type of activities in the Republic of Macedonia. The need of such analysis resulted from the fact that this region comprises 8 % of the Republic's territory and has established itself as an influential agricultural and economic region in the wider vicinity as well. For this purpose adequate methods were utilised such as: mathematical-statistical, cartographic, climatological, touristic, etc. One of the pillars of these research activities, which support the essential postulates of the effort, was the long-lasting terrain exploration. It all points to the final conclusion that the Tikvesh Basin features quite favourable natural and socio-geographical factors which enhance development of vine-growing, winery and wine tourism, whose outstanding potential has only modestly been utilised so far.
Keywords: L83; 330; Tikvesh Basin; Viniculture; Wine Tourism